Consideraciones ontotecnológicas sobre el ser humano y la Inteligencia Artificial - Marta Sánchez Viejo (Claridades: Revista de Filosofía)
Technology has biases and is inserted in discursive and metaphorical networks that influence its own meaning and that of the participating actors. The elements that are part of these technological fabrics and generate associations are not accidental, they are supportive of modern science and are mediated by issues such as the idea of objectivity or neutrality. Reconsidering the relationships between humans and technology allows us to adopt a new ontological perspective that questions the traditional separation between subject and object and historically established identities in order to understand the human being as a situated and performative entity. This article will try to unravel what links, similarities, symmetries and differences exist between the human and non-human, focusing on the technological field and, specifically, AI. To do this, a framework supportive of actor-network theory is used and human-AI associations and the agency of AI on the delimitation of the subject are explored.